2020
DOI: 10.1088/1741-4326/ab9255
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability of the ITER 15 MA scenario against the alpha fishbone

Abstract: The stability of the n = m = 1 alpha-fishbone kinetic-MHD mode on the ITER 15 MA baseline scenario (ITER Physics Expert Group on Energe Drive and ITER Physics Basis 1999 Nucl. Fusion 39 2471-95) is analyzed using the non-linear hybrid kinetic-MHD code XTOR-K. Quantitative agreement is found between the complex frequencies ω + iγ computed with the linear model in (Brochard G. et al 2018 J. Phys.: Conf. Series 1125 012003) and XTOR-K's linear simulations. Identical precessional resonance positions in phase space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…The number of particle is integrated over unit surface (x and y directions are subdivided into 100 pieces for the integration). for similar conditions of fast particles of 1 MeV in ITER [20,21]. In this linear study, no resonance is found with passing particles but a resonance with trapped particles destabilize the n = 1 fishbone mode.…”
Section: Nbi Impact In An Iter-like Casementioning
confidence: 57%
See 4 more Smart Citations
“…The number of particle is integrated over unit surface (x and y directions are subdivided into 100 pieces for the integration). for similar conditions of fast particles of 1 MeV in ITER [20,21]. In this linear study, no resonance is found with passing particles but a resonance with trapped particles destabilize the n = 1 fishbone mode.…”
Section: Nbi Impact In An Iter-like Casementioning
confidence: 57%
“…It is likely that the destabilization of fishbones ("fishbone branch" with growth rates increasing with β f p , as observed in Ref. [21]) requires unrealistically large fast particle pressure for this plasma configuration.…”
Section: A Impact Of Fast Particles On the N = 1 Modementioning
confidence: 72%
See 3 more Smart Citations